Static size effect of recycled coarse aggregate concrete: Experimental study, meso-scale simulation, and theoretical analysis. (December 2021) - Zhou, Hongyuan; Zhou, Houzhan; Wang, Xiaojuan; Cao, Wanlin; Song, Tianyi; Qiao, Qiyun
Abstract: Although fruitful research results have been achieved on the investigation of size effect of natural coarse aggregate concrete (NAC), limited research is devoted to the study on size effect of recycled coarse aggregate concrete (RAC). Meanwhile, the feasibility of applying these results on NAC to RAC is questionable. To this end, a synthesis of experimental studies with different recycled coarse aggregate (RCA) substitute rates (0%, 30%, 50%, 70% and 100%), different prismatic sizes of 70 × 70 × 210, 100 × 100 × 300, 150 × 150 × 450 and 200 × 200 × 600 mm are carried out to investigate the size effect of RAC with consideration of the influence of substitute rate. As a powerful complement to the experimental study, the meso-scale numerical simulation is carried out. These results show that increasing the specimen size and RCA substitute rate both leads to decreasing nominal compressive strength of RAC. Furthermore, the meso-scale numerical simulation results show that the oblique concentrated damage zone is more likely to form in the specimens with higher RCA substitute rates, which exhibits more significant size effect. In addition, the size effect law of RAC is established based on the empirical formula and back-propagation neural network, respectively, both providing an accurate prediction of nominal compressive strength of RAC with consideration of specimen size and RCA substitute rate, and the results provide some references for the design specification of RAC members.